(Re)framing sustainable transitions: perspectives from a city in the global South - Roux, Saul (Department of Environmental and Geographical Science, 2019)
This study analyses the conditions under which socio-technical systems transition to more sustainable configurations. It does so through an exploration of the City of Cape Town’s electricity distribution arrangements. This investigation is situated within debates on sustainable socio-technical transitions in general and the multi-level perspective (MLP) in particular. This study considers four themes that are important for understanding the conditions under which socio-technical regimes change - regulation, organisations, geographical context and scale. These themes structure an empirical study of an energy transition in a city (scale) in the Global South (geographical context) and an examination of the role of regulatory and organisational conditions in shaping sustainable transitions. In turn, the implications of this case for transition theories is explored. The site of the study is a local government in an African city, Cape Town. This southern geography offers unique conditions, particularly related to the ways in which the technical interacts with the social, in conditions where poverty and inequality are prevalent. In exploring the City’s electricity system, field-work was undertaken using a participatory, engaged and grounded theory approach. Notably, research was conducted within a knowledge co-production setting that involved spending three years in the City, embedded in its Energy and Climate Change Unit. This provided invaluable access to the tacit knowledge of practitioners and a unique view into the internal workings of the City. The results of this field-work have implications for sustainable transition theory. In the City, systemic tensions and contestation were prominent in relation to the incumbent electricity system. Notably, it was found that reconfiguration agendas, represented in the City’s Energy and Climate Action Plan, are disrupting developmental values, such as cross-subsidisation, which underpin the incumbent electricity system. Accordingly, regime reconfiguration based on environmental values competes with developmental values embedded within incumbent regime structures. This provides the basis for conceptualising socio-technical transitions as conflicts related to contested values. These value tensions are repeated across scales, manifested by contestation between urban energy autonomy and security on the one hand and national developmental transitions on the other. The presence of systemic value tensions in the City also has a bearing on the conditions and pathways for socio-technical transitions. In this regard, this study applies a constructivist approach to exploring socio-technical reconfigurations through identifying two broad energy trajectories that the City is able to pursue; a centralised or distributed trajectory. This informs a heuristic to explore the socio-economic outcomes of reconfigurations. It further identifies potential reconfiguration processes present in the City that forms the basis of alternative theoretical reconfiguration typologies that are cognisant of value contestations. Through evaluating formal rules that regulate the City’s electricity system, this study finds that regulatory systems are used as a tool to assimilate, codify and stabilise dominant value sets into socio-technical regimes. Further, it was found that separate City departments are aligned to divergent socio-technical values. Thus, competing values create contestation within organisations in framing transition processes. Overall, the study offers an alternative conceptualisation of socio-technical regimes as systems produced and reproduced through value contestation. By drawing on the case of the City’s electricity system, the study provides evidence to show that value tensions related to socio-technical regimes are played out in regulatory, organisational and political landscapes. The study thus argues that these competing value systems are integral in the co-evolutionary process of regime configuration and reconfigurations.